FREQUENCY OF WOUND INFECTIONS IN HIGH-RISK PATIENTS UNDERGOING OBSTETRIC AND GYNECOLOGY SURGERIES COMBINED MILITARY HOSPITAL, PESHAWAR (The Research of Medical Science Review, 2024)
Surgical site infection (SSI) is among the most frequent and consequential postoperative gynecological complications to date and is still a major public health concern. It remains a significant cause of morbidity; it complicates 2–5% of open gynecological operations. Objective: Thus, the objective of this study was to establish the prevalence of SSIs in high risk obstetric and gynecological patients who underwent surgery. Study Design: Descriptive case series Study Settings and Duration: The study was performed at the Department of Obstetrics & Gynecology, Combined Military Hospital, Peshawar from 7 November 2021 to 7 May 2022. Materials and Methods: Participants were mainly women who had been operated via obstetric or gynecologic surgeries, and their SSIs were observed for 15 postoperative days. The symptoms/clinical presentation of SSI, including erythema, induration and slight discharge at the site of the incision were also assessed. Data was analyzed using SPSS. Results: The analysis included 157 patients who met the inclusion criteria before undergoing the interventions. There were 83 participants, the age was distributed between 30 and 70 years and the mean age was 40.11 years old (SD ± 13.37). They noted surgical site infection in 52 patients giving a rate of 33. 1%. Conclusion: The findings of the study also identified that the overall SSIs were high (33.1%). This higher rate may be explained by poor socio-economic status, poor Nutritional health and other related co morbidities.